2010
DOI: 10.1523/jneurosci.0303-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Exacerbate Lipopolysaccharide-Induced Signaling in the Frontal Cortex and Hippocampus in a Dose-Dependent Manner

Abstract: Although the anti-inflammatory actions of glucocorticoids (GCs) are well established, evidence has accumulated showing that proinflammatory GC effects can occur in the brain, in a poorly understood manner. Using electrophoretic mobility shift assay, real-time PCR, and immunoblotting, we investigated the ability of varying concentrations of corticosterone (CORT, the GC of rats) to modulate lipopolysaccharide (LPS)-induced activation of NF-B (nuclear factor B), expression of anti-and proinflammatory factors and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
111
0
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(128 citation statements)
references
References 56 publications
9
111
0
8
Order By: Relevance
“…The mechanisms by which chronic excessive corticosterone exerts pro-inflammatory effects have been well investigated by one study group (Sorrells et al, 2009). Munhoz et al reported that chronically increased corticosterone mediates increased expression of nuclear factor-κB (NF-κB), mitogen-activated kinase (MAPK), and proinflammatory cytokines, which consequently contributes to a sustained inflammatory state (Munhoz et al, 2010). In a recent study, Sorrell et al reported that corticosterone exacerbates inflammation, thereby inducing detrimental effects on the hippocampus (Sorrells et al, 2014).…”
Section: Influences Of Chronically Elevated Glucocorticoid Levelsmentioning
confidence: 99%
“…The mechanisms by which chronic excessive corticosterone exerts pro-inflammatory effects have been well investigated by one study group (Sorrells et al, 2009). Munhoz et al reported that chronically increased corticosterone mediates increased expression of nuclear factor-κB (NF-κB), mitogen-activated kinase (MAPK), and proinflammatory cytokines, which consequently contributes to a sustained inflammatory state (Munhoz et al, 2010). In a recent study, Sorrell et al reported that corticosterone exacerbates inflammation, thereby inducing detrimental effects on the hippocampus (Sorrells et al, 2014).…”
Section: Influences Of Chronically Elevated Glucocorticoid Levelsmentioning
confidence: 99%
“…The role of p38MAPK may also be involved in the regulation of inflammatory signaling by other hormones including melanocortin stimulating hormone (Gonzalez et al, 2009) and glucocorticoids. The role here is not straightforward, however, as activity of this kinase is increased by both inflammatory stimulation, and glucocorticoid receptor activation (Munhoz, Sorrells, Caso, Scavone, & Sapolsky, 2010). Multiple mediators of inflammatory signaling, therefore, converge onto p38MAPK and JNK activation, suggesting that this pathway may integrate information from not just individual cytokines, but patterns of cytokine activity.…”
Section: Kinase Signaling and Transcriptional Regulationmentioning
confidence: 99%
“…Glucocorticoids have a wide range of peripheral and central effects including the enhancement of neuroinflammation and ischemic injury. [27] The peripheral neuroendocrine response is propagated centrally via either the neural pathway (vagus nerve) activated by the HPA axis or the humoral pathway by peripheral mediators crossing the blood brain barrier. With respect to the humoral pathway, there is some evidence that peripheral mediators impact the brain at the choroid plexus and circumventricular organs leading to the production of proinflammatory cytokines in the brain.…”
Section: Pathophysiologymentioning
confidence: 99%